Effect of Polyherbal Feed Supplementation on Growth Performances of Assam Hill Goat - , Chinmoy Dutta; , Jyoti Prasad Bordoloi; , Raj Jyoti Deka; , Naba Jyoti Deka (Archives of Current Research International, 2025)
In the current investigation, 36 nos of Assam Hill goat were selected and divided randomly into three groups. Polyherbal feed was supplemented in treatment groups @ 1 and 2 g/Kg body weight from 4 month of age till 12month of age, respectively. Data on various parameters were analysed at fortnightly interval for a period up to 9 months. The average body weight at 19th fortnight i.e., at 12months of age were 13.84± 0.032, 14.47±0.021 and 16.24±0.040 kg in control and the two treatment groups, T1 and T2 respectively. The overall body weight (kg) of two treatment groups were significant higher (p<0.01) than that of control group. In respect of sex, the male animals attained higher bodyweight than that of female animals at all the stages of experiment. Significant differences (p<0.01) among control and two treatment groups were observed for body length and chest girth of the animals. The study indicated that polyherbal feed supplementation improve the overall growth of the Assam Hill goats.